The determination of plasticizer in PVC soft toy and Teether / Nur Fadhilah Che Mohamad - Che Mohamad, Nur Fadhilah (2008)
This project paper studies on the types of plasticizer in the PVC soft toy and teether. In this project, the both samples which are rubbery duck and teether are extracted first from polymer using the Soxthlet extraction apparatus and then analyzed using various techniques. The UV/visible Spectroscopy is used for characterization of extractant where the number of peak arises show the component of additives in both samples. The characterization of the plasticizer is then analyzed using IR Spectroscopy that shows the functional groups presence in the both samples. Thus, the possibly plasticizer that added to the both samples can be determine. The possibly plasticizer that added to the rubbery duck is Dibutyl Sebacate(DBS) which is sebacate based plasticizer. For the teether sample, the possibly separation components is Methoxy Phenol.